Efficacy of Presurgical Nasoalveolar Molding in Bilateral Cleft Lip and Palate: A Case Report - Parastoo Namdar; Atena Shiva; Mojtaba Namdar; Azam Haddadi Kohsar (Journal of Mazandaran University of Medical Sciences, 2023)
Cleft lip and palate as one of the most common congenital malformations of the oral cavity is affected by genetic and environmental factors. Subsequent aspiration during feeding, aesthetic, speech, or functional problems, and dental malformations are the main problems of neonates born with cleft lip and palate. The management of neonates with cleft lip and palate has been remarkably improved in recent years. The use of modern surgical techniques and its combination with such methods as presurgical nasoalveolar molding (NAM) is on the rise. The efficacy of preoperative casting in repairing deformed nasal cartilage in neonates with cleft lip and palate has been confirmed based on the literature. Here, we present the case of a 20-day-old neonate with bilateral cleft lip and palate who underwent presurgical nasoalveolar molding to facilitate feeding and recover facial appearance. The bony cleft of maxillary segments in the child was molded and repositioned with a combination of extra-oral elastic and intra-oral appliances. Elastic forces caused backward pressure against the protruding pre-maxilla  and careful use of forces on the cleft segments improved their positions and allowed definitive muscles and lip repair. In this technique, a nasal stent was attached to the intra-oral mouth plate and was designed to improve nasolabial anatomy.